Need for Extensive Training in Soil Conservation - Pandey, S.N. (Journal of Soil and Water Conservation, 2022)
The Soil and Water Conservation on croplands, grasslands, _ forests, and gullied areas is the key to make our land more productive and our nation prosperous. The wise and skilful manage-ment of the land depends on the land owners and farmers. It is, therefore, more essential to develop complete consciousness about soil and water conservation among the land owners and farmers, so that they understand the importance of this concept, It is not enough to execute the soil conservation work on the problem areas but the people in the region are to be trained, educated and helped to enable them to utilize the resources efficiently, since thz future follow up programme and maintenance depcnd on the people of the region.